[tex]$(1-3a)^2-(1+3a)(3a-1)=(1-3a)^2+(1+3a)(1-3a)=(1-3a)(1-3a+1+3a)=2(1-3a)=2-6a$[/tex]
[tex]\displaystyle\bf\\(1-3a)^{2} -(1+3a)(3a-1)=\\\\=1^{2} -2\cdot 1\cdot 3a+(3a)^{2}-(3a+1)(3a-1)= \\\\=1-6a+9a^{2} -\Big[(3a)^{2} -1^{2} \Big]=1-6a+9a^{2} -(9a^{2}-1)=\\\\=1-6a+9a^{2}-9a^{2} +1=2-6a[/tex]
При упрощении выражения были применены формулы :
[tex]\displaystyle\bf\\1)\\\\(a-b)^{2} =a^{2} -2ab+b^{2} \\\\2)\\\\(a+b)(a-b)=a^{2} -b^{2}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]$(1-3a)^2-(1+3a)(3a-1)=(1-3a)^2+(1+3a)(1-3a)=(1-3a)(1-3a+1+3a)=2(1-3a)=2-6a$[/tex]
Verified answer
[tex]\displaystyle\bf\\(1-3a)^{2} -(1+3a)(3a-1)=\\\\=1^{2} -2\cdot 1\cdot 3a+(3a)^{2}-(3a+1)(3a-1)= \\\\=1-6a+9a^{2} -\Big[(3a)^{2} -1^{2} \Big]=1-6a+9a^{2} -(9a^{2}-1)=\\\\=1-6a+9a^{2}-9a^{2} +1=2-6a[/tex]
При упрощении выражения были применены формулы :
[tex]\displaystyle\bf\\1)\\\\(a-b)^{2} =a^{2} -2ab+b^{2} \\\\2)\\\\(a+b)(a-b)=a^{2} -b^{2}[/tex]